2020
DOI: 10.1021/jacs.9b11453
|View full text |Cite
|
Sign up to set email alerts
|

Chiral 2D Organic Inorganic Hybrid Perovskite with Circular Dichroism Tunable Over Wide Wavelength Range

Abstract: The effect of chemical-composition modification on the chiroptical property of chiral organic ammonium cation-containing organic inorganic hybrid perovskite (chiral OIHP) is investigated. Varying the mixing ratio of bromide and iodide anions in Sor R-C 6 H 5 CH 2 (CH 3 )NH 3 ) 2 PbI 4(1−x) Br 4x modifies the band gap of chiral OIHP, leading to a shift of the circular dichroism (CD) signal from 495 to 474 nm. However, it is also found that an abrupt crystalline structure transition occurs, and the CD signal is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(231 citation statements)
references
References 35 publications
11
211
0
Order By: Relevance
“…In contrast, the 1D chain extends to the carrier transporting direction in the device, resulting in the higher photoconductivity than 2D structure. In addition, the high photoconductivity in the helical 1D structure under CPL irradiation probably depends on the direction of the polarized electronic spin generated by selective absorption of CPL with angular momentum ( 17 , 28 ). These effects have been reported in chiral perovskites with strong spin-orbit coupling, which can be explained by spin-dependent optical selection rules and large Rashba splitting ( 29 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the 1D chain extends to the carrier transporting direction in the device, resulting in the higher photoconductivity than 2D structure. In addition, the high photoconductivity in the helical 1D structure under CPL irradiation probably depends on the direction of the polarized electronic spin generated by selective absorption of CPL with angular momentum ( 17 , 28 ). These effects have been reported in chiral perovskites with strong spin-orbit coupling, which can be explained by spin-dependent optical selection rules and large Rashba splitting ( 29 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first structural report for 1D and 2D chiral perovskites was presented as a single crystal by Billing et al (14,15) in 2013. Ahn et al (16,17) demonstrated the chiroptical property in 2D chiral perovskites, (R-or S-1-PEA) 2 PbI 4 , by measurements of CD signals. The chiral ligand, R-or S-1-PEA + , also forms 1D chiral perovskites as (R-or S-1-PEA)PbI 3 , and the CPL photodetector based on 1D chiral perovskite was reported by Chen et al (18).…”
Section: Introductionmentioning
confidence: 99%
“…The growing attention to chiral materials is connected with their potential applications in the area of chiral optoelectronics and spintronics. Chirality is associated with the phenomenon of circular dichroism (CD) 2 since enantiomer pairs absorb left and right circularly polarized light differently [3][4][5][6][7] , and enantiomers can also emit circularly polarized light in the absence of an external magnetic field. [8][9][10] Recently chiral materials have been used in spintronic devices as a spin filters due to chiral-induced spin selectivity.…”
mentioning
confidence: 99%
“…To achieve optimized materials properties of 2DHPs, in addition to tuning the chemical compositions of inorganic metal cations, an alternative method is to use molecular engineering, i.e., incorporation of organic ligands and the utilization of the intramolecular and/or intermolecular interactions in the 2DHPs. As indicated by recent work, [ 232–236 ] such a route could lead to enhanced electronic and optical properties and improved stability. For example, Passarelli et al reported an enhanced out‐of‐plane conductivity and photovoltaic performance in the layered (aromatic‐O‐linker‐NH 3 ) 2 PbI 4 .…”
Section: Discussionmentioning
confidence: 99%